Pembangunan dan Demokratisasi Papua - Binsar Sianipar, Prof. Dr. Der Soz Gumilar Rusliwa Somantri (Novateur Publications, 2022)
The purpose of this article is to discuss conflict resolution in Papua in order to promote the government’s sustainable development objectives.One of the roots of the conflict in Papua is the disappointment amongst the Papuan due to economic and social discrepancies as well as cultural disharmony which resulted from uneven development in the region. The disappointment can only be resolved through accelerated development as to where the Papuans are able to enjoy justice and prosperity. However, it is impossible to execute a sustainable development program in the absence of political stability and security. Therefore, it is imperative to reorient the resolution of conflicts in Papua through diplomacy, both internationally and domestically, to gain a common ground and agreement between the conflicting parties in order to create political stability and security.
Keywords: conflict, sustainable development, Papua